2019
DOI: 10.1002/ijc.31979
|View full text |Cite
|
Sign up to set email alerts
|

Mutated EPHA2 is a target for combating lymphatic metastasis in intrahepatic cholangiocarcinoma

Abstract: Exploring the genetic aberrations favoring metastasis is important for understanding and developing novel strategies to combat cancer metastasis. It remains lack of effective treatment for the dismal prognosis of intrahepatic cholangiocarcinoma (ICC). Here, we aimed to study genetic alternations during lymph node metastasis of ICC and investigate potential mechanisms and clinical strategy focused on mutations. We performed whole‐exome sequencing and transcriptome sequencing on samples from 30 ICC patients, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…ALW-II-41-27, a novel EphA2 tyrosine kinase inhibitor 30 , has obvious anti-tumor effects in the many types of cancers 31 36 . Previous studies indicate that ALW-II-41-27 suppresses cancers by targeting S879 phosphorylation of EphA2 32 , 34 , 36 . As our results showed that pY772-EphA2 plays a role in NPC growth, we detected whether pY772-EphA2 is a target of ALW-II-41-27.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…ALW-II-41-27, a novel EphA2 tyrosine kinase inhibitor 30 , has obvious anti-tumor effects in the many types of cancers 31 36 . Previous studies indicate that ALW-II-41-27 suppresses cancers by targeting S879 phosphorylation of EphA2 32 , 34 , 36 . As our results showed that pY772-EphA2 plays a role in NPC growth, we detected whether pY772-EphA2 is a target of ALW-II-41-27.…”
Section: Resultsmentioning
confidence: 99%
“…Various therapeutic strategies targeting EphA2, such as EphA2 antibody, ligand Ephrin-A1, Ephrin-A1 mimic peptides, and RNA interference, have been developed 41 . It has been reported that EphA2 tyrosine kinase inhibitor, ALW-II-41-27 30 , has obvious anti-tumor effects in the many types of cancers [31][32][33][34][35][36] . As an EphA2 tyrosine kinase inhibitor, whether ALW-II-41-27 suppresses cancers by inhibiting pY772-EphA2 is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 4 , 5 , 6 It is the subordinate most extensive hepatic malignancy after hepatocellular carcinoma, accounting for 15%–20% of primary hepatobiliary malignancies, and the overall incidence of CHOL seems to be increasing worldwide. 7 , 8 , 9 , 10 Most patients have advanced-stage disease at presentation, and the majority of patients with CHOL have a dismal prognosis; surgical resection is the preferred treatment option for patients who have early-stage disease, not for those at late or advanced stages because available systemic therapies are of limited effectiveness. 11 , 12 , 13 Therefore, increased understanding of its molecular tumor biology is urgently required.…”
Section: Introductionmentioning
confidence: 99%